Stunting or runting syndrome in broiler chickens and its pathological changes - Wahyuwardani, S; Sani, Y; Parede, L; Syafriati, T; Poeloengan, M (Indonesian Journal of Animal and Veterinary Sciences, 2000)
A disease with stunting or runting syndrome in broiler chickens was investigated in 13 districts of West Java and Central Java provinces. A total of 291 chickens samples both with clinically stunted or runted were collected from 37 poultry farms. Blood samples were collected randomly from chickens in poultry farms for packed cells volume analysis. Tissues of liver, spleen, thymus, proventriculus, ventriculus intestines, caecum, pancreas, bursa fabricious and heart were collected for histopathological examination. Field surveys showed that prevalence rate of stunting or runting syndrome was varied from one farm to others between 0,1% to 50%. Clinical signs were noted as ununiformity of body size in a flock of chicken, stunted and/or runted of body weight gain and protrude of wing feather. Pathologic changes were hyperemic thymus, athropic thymus and athropic pancreas. While microscopically included dilatation crypt of Lieberkuhn, inflammation of thymus, pancreatitis and enteritis variably among each locations. The PCV level did not show direct link to the affected stunting or runting syndrome. Â  Key words: Syndrome, stunting, runting, pathology anatomy, histopathology